2020
DOI: 10.1021/jacs.9b08822
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and Stereochemical Control of Peptidoglycan Cross-Linking by Transpeptidation by Escherichia coli PBP1B

Abstract: Penicillin binding proteins (PBPs) catalysing transpeptidation reactions that stabilize the peptidoglycan component of the bacterial cell wall are the targets of -lactams, the most clinically successful antibiotics to date. However, PBP-transpeptidation enzymology has evaded detailed analysis, because of the historical unavailability of kinetically competent assays with physiologically relevant substrates and the previously unappreciated contribution of protein cofactors to PBP activity. By re-engineering pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…An elegant recent report (Catherwood et al, 2020) described the use of a coupled D-Ala release assay to determine the kinetic parameters of the TPase activity of PBP1B Ec against different substrates and this study also confirmed the previously reported activation of the TPase of PBP1B by LpoB in the presence of detergents (Egan et al, 2014, Egan et al, 2018, Lupoli et al, 2014. The authors of the recent report (Catherwood et al, 2020) discussed that the LpoB-mediated TPase activation explains the essentiality of LpoB for PBP1B function in the cell. However, this view ignores previously published data demonstrating that the essentiality of LpoB can be readily explained by its primary effect, the >10-fold stimulation of PBP1B's GTase (Egan et al, 2014).…”
Section: Coupled Reactions In Class a Pbssupporting
confidence: 78%
See 2 more Smart Citations
“…An elegant recent report (Catherwood et al, 2020) described the use of a coupled D-Ala release assay to determine the kinetic parameters of the TPase activity of PBP1B Ec against different substrates and this study also confirmed the previously reported activation of the TPase of PBP1B by LpoB in the presence of detergents (Egan et al, 2014, Egan et al, 2018, Lupoli et al, 2014. The authors of the recent report (Catherwood et al, 2020) discussed that the LpoB-mediated TPase activation explains the essentiality of LpoB for PBP1B function in the cell. However, this view ignores previously published data demonstrating that the essentiality of LpoB can be readily explained by its primary effect, the >10-fold stimulation of PBP1B's GTase (Egan et al, 2014).…”
Section: Coupled Reactions In Class a Pbssupporting
confidence: 78%
“…A limitation of the recent kinetic study is that authors used assay conditions (e.g. very low enzyme concentration) at which PBP1B Ec is virtually inactive without an activator (Catherwood et al, 2020) as demonstrated previously (Pazos et al, 2018, Muller et al, 2007, thus the study likely substantially overestimated the extent of TPase activation by LpoB. P. aeruginosa uses a structurally different lipoprotein activator, LpoP, to stimulate its PBP1B (Greene et al, 2018).…”
Section: Coupled Reactions In Class a Pbsmentioning
confidence: 98%
See 1 more Smart Citation
“…The formation of these crosslinks occurs primarily during the polymerization of the murein subunits and is facilitated by a family of transpeptidase enzymes. The four primary transpeptidases of E. coli have only recently been quantitatively characterized in vivo, via liquid chromatography mass spectrometry, which revealed a notably slow kinetic turnover rate of˘2 crosslinking reactions formed per second per enzyme as noted above (Catherwood et al, 2020).…”
Section: Peptidoglycan Synthesismentioning
confidence: 93%
“…Furthermore, we hope that this cryoEM methodology will allow for the capture of structural information regarding the native acceptor and donor substrates, which have largely eluded crystallization in both class A and class B PBPs. Structural insight into these acceptor and donor substrates will allow for further appreciation of recent work to unravel these mechanisms through the use of continuous assays 21 and allow for the development of novel antibacterial compounds that target GTase activity. We believe that the work presented in this manuscript will revitalize the study of class A PBPs and that this and subsequent work will be of great assistance as we attempt to ward off a post-antibiotic era.…”
Section: Resultsmentioning
confidence: 99%